Factors influencing self-reported use of mouthwashes among dental patients in Amman, Jordan - Hamdan, Ahmad (Jordan Medical Journal, 2019)
Aims: to assess the extent of mouthwash self-reported use and to evaluate the sociodemographic factors affecting this behavior. Methods: A survey was conducted with 317 patients aged 16-76 years attending the Department of Dentistry, University of Jordan Hospital. Sociodemographic data, self-reported general and oral health status, oral hygiene methods, and data on mouthwash use were collected. Results: The prevalence of self-reported use of mouthwash was 44.8%. Female patients used mouthwashes more frequently and there was nearly 2% increase in the chance of using mouthwash with each one-year increase in patient’s age. Only self-reported gingival inflammation was associated with self-reported mouthwash use (P=0.044). Conclusion: The findings showed that mouthwash use could be influenced by age and gender and could be associated with patient’s perception of his/her gingival condition. There is a need for larger scale studies to elucidate the different factors influencing mouthwash use and the role it could play in the programs of oral hygiene promotion.